Nexus between Financial Development and Economic Prosperity in Selected Countries of Emerging and Developing Asia - Budhathoki, Prem Bahadur; Bhattarai, Ganesh; Dahal, Arjun Kumar (Nepal Journal of Multidisciplinary Research, 2024)
Background: The link between financial development and economic growth remains debated in theoretical and empirical research. This research focuses on developing and emerging Asian nations to determine the impact of financial development on economic growth. Methods: This study took a sample of six member countries from SAARC and BIMSTEC, covering the period from 1990 to 2021, resulting in 192 observations. It employs a descriptive and correlation matrix to examine the distribution and association between predictor and response variables. This study tests the "Finance-led growth theory" using FMOLS and DOLS estimators. Results: The findings indicate a significant positive effect of financial development on economic growth, assessed through two measures: financial institution development and financial market development. Foreign direct investment has a positive effect on economic growth. In contrast, age dependency, "young," has an adverse and noteworthy impact on economic prosperity. Similarly, export and personal remittance have an unfavorable yet negligible effect on economic growth. Conclusion: Financial institutions and financial market development positively and significantly affect economic growth in emerging and developing Asia and support the "Finance-led growth theory." Novelty: This study employs two metrics—financial institution and financial market development—to assess the link between financial development and economic growth and offers ample literature in the context of emerging and developing Asia.